2017
DOI: 10.1042/bcj20170389
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms linking SIRT activity and hypoxic 2-hydroxyglutarate generation: no role for direct enzyme (de)acetylation

Abstract: 2-hydroxyglutarate (2-HG) is a hypoxic metabolite with potentially important epigenetic signaling roles. The mechanisms underlying 2-HG generation are poorly understood, but evidence suggests a potential regulatory role for the sirtuin family of lysine deacetylases. Thus, we hypothesized that the acetylation status of the major 2-HG-generating enzymes (lactate dehydrogenase (LDH), isocitrate dehydrogenase (IDH) and malate dehydrogenase (MDH)) may govern their 2-HG generating activity. In-vitro acetylation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…However, IDH2 activity was only found reduced in the liver but not in the inner ear and brain of SIRT3 KO mice ( Someya et al, 2010 ). In contrast, it was recently reported that in vitro acetylation of purified IDH2 from the porcine heart increased its activity ( Nadtochiy et al, 2017 ). These results suggest that acetylation of IDH2 influences its enzymatic activity in a tissue-dependent manner; deacetylation increases its activity in the kidney and liver but decreases its activity in the heart and has no effect in the inner ear and brain.…”
Section: Sirt3 Regulates Mitochondrial Bioenergeticsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, IDH2 activity was only found reduced in the liver but not in the inner ear and brain of SIRT3 KO mice ( Someya et al, 2010 ). In contrast, it was recently reported that in vitro acetylation of purified IDH2 from the porcine heart increased its activity ( Nadtochiy et al, 2017 ). These results suggest that acetylation of IDH2 influences its enzymatic activity in a tissue-dependent manner; deacetylation increases its activity in the kidney and liver but decreases its activity in the heart and has no effect in the inner ear and brain.…”
Section: Sirt3 Regulates Mitochondrial Bioenergeticsmentioning
confidence: 94%
“…However, Zhao et al (2010) reported that acetylation of MDH increased its enzymatic activity in Chang liver (HeLa derivative) and HEK293 cells. Interestingly, neither acetylation nor deacetylation had any effect on the enzymatic activity of purified bovine heart MDH2 ( Nadtochiy et al, 2017 ). These results suggest that, like IDH2, the effects of acetylation on the MDH enzymatic activity are tissue-dependent.…”
Section: Sirt3 Regulates Mitochondrial Bioenergeticsmentioning
confidence: 98%
See 2 more Smart Citations
“…We recently showed that the SIRT1 inhibitor splitomicin (Sp) causes mild cellular alkalinization in primary mouse cardiomyocytes 16 . In companion experiments, we also tested the effects of the SIRT1 activator NMN, and surprisingly found that 1 mM NMN induced cellular acidification ( Figure 1A/B).…”
Section: Resultsmentioning
confidence: 99%